(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic kidney disease (CKD) is a frequent but under-recognized comorbidity in severe chronic obstructive pulmonary disease (COPD). We aimed to determine the prevalence of renal dysfunction and its association with comorbid conditions in patients hospitalized with severe COPD.